PENGEMBANGAN BUKU AJAR KALKULUS DERIVATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA - Muhammad Taqwa (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This research aims to develop valid and practical textbooks to improve students' understanding of concepts. This type of research is development research, namely the development of textbooks with the Plomp model: (1) initial investigation, (2) design, (3) realization/construction, (4) testing, evaluation and revision, and (5) implementation. The subject of this study is a student of the Mathematics Education Study Program of STKIP Andi Matappa. Research instrument: textbook validation sheet. Results of the study: (1) the validity score of the content and reliability of the textbook is included in the high category; (2) This textbook has practical criteria; (3) There is an increase in students' understanding of the concept with the average student being in the medium category. The derivative calculus textbook has met the criteria of valid, reliable and practical to improve the understanding of the concept of STKIP Andi Matappa students.